Ogg Vorbis sebagai Salah Satu Alternatif Metode Pemampatan Suara Merugi - Azis Wisnu Widhi Nugraha (Jenderal Soedirman University, 2006)
Multimedia technology has changed rapidly. How to get a small audio file with the high quality that still equal to the real quality is became the common issue in the sound compression world. Because the human ears can't hear all of sound component, it's allowed to compress an audio data using lossy method. A new lossy method to compress an audio data is Ogg Vorbis. This method has its own psychoacoustic model that made this method has the better sound quality if compared to the popular codec Mp3.